2005
DOI: 10.1016/j.ejpoleco.2004.02.003
|View full text |Cite
|
Sign up to set email alerts
|

A reappraisal of the inflation–unemployment tradeoff

Abstract: This paper offers a reappraisal of the inflation-unemployment tradeoff, based on "frictional growth," describing the interplay between nominal frictions and money growth. When the money supply grows in the presence of price inertia (due to staggered wage contracts with time discounting), the price adjustments to each successive change in the money supply are never able to work themselves out fully. In this context, monetary shocks have a gradual and delayed effect on inflation, and these shocks also generate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 67 publications
(107 reference statements)
2
49
0
Order By: Relevance
“…3 8 See Karanassou et al (2005) for an empirical appraisal of the long-run Phillips curve, or Beyer and Farmer (2007) for a positive empirical relationship between inflation and unemployment. Vaona (2012) finds empirical support for a negative relationship between inflation and output growth.…”
Section: The Cost Of Price Dispersion and The Long-run Implications Omentioning
confidence: 99%
“…3 8 See Karanassou et al (2005) for an empirical appraisal of the long-run Phillips curve, or Beyer and Farmer (2007) for a positive empirical relationship between inflation and unemployment. Vaona (2012) finds empirical support for a negative relationship between inflation and output growth.…”
Section: The Cost Of Price Dispersion and The Long-run Implications Omentioning
confidence: 99%
“…80 Karanassou, Sala and Snower (2003) find considerable long-run trade-off between inflation and unemployment in a model with nominal price staggering and money growth.…”
mentioning
confidence: 99%
“…The results also showed that in those countries where long-term unemployment was high, the long-term unemployment played a little role in the setting of prices and wages. Karanassou, Sala, & Snower (2005) re-examined the interactive relationship between inflation and www.ccsenet.org/ijef International Journal of Economics and Finance Vol. 5, No.…”
Section: Theoretical and Empirical Literature About Inflation-unemplomentioning
confidence: 99%